2016
DOI: 10.1007/s40572-016-0083-2
|View full text |Cite
|
Sign up to set email alerts
|

Of Pesticides and Men: a California Story of Genes and Environment in Parkinson’s Disease

Abstract: At the start of the post-genomics era, most Parkinson’s disease (PD) etiology cannot be explained by our knowledge of genetic or environmental factors alone. For more than a decade, we have explored gene-environment (GxE) interactions possibly responsible for the heterogeneity of genetic as well as environmental results across populations. We developed three pesticide exposure measures (ambient due to agricultural applications, home and garden use, occupational use) in a large population-based case-control stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 99 publications
(111 reference statements)
3
76
2
Order By: Relevance
“…While genetic risks have been identified, environmental factors and gene-environment interactions likely account for most PD cases (Nalls et al, 2014; Ritz et al, 2016). We provide evidence that the gut microbiota are required for postnatal events that promote hallmark motor deficits in an animal model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While genetic risks have been identified, environmental factors and gene-environment interactions likely account for most PD cases (Nalls et al, 2014; Ritz et al, 2016). We provide evidence that the gut microbiota are required for postnatal events that promote hallmark motor deficits in an animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological functions in affected individuals, such as altered intestinal absorption, reduced gastric motility, or dietary habits, represent factors that may change the microbiome. Epidemiological evidence has linked specific pesticide exposure to the incidence of PD (Ritz et al, 2016), with some pesticides known to impact microbiome configuration (Gao et al, 2016). Given the structure of αSyn and its ability to associate with membranes (Jo et al, 2000), it is tempting to speculate that extracellular αSyn may act as an antimicrobial, similar to recent observations with amyloid beta (Kumar et al, 2016), and shape the PD microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…First, when estimating the effect of occupational pesticide use we adjusted for other sources of pesticide exposure (frequent household use, ambient workplace, ambient residential) or mutually adjusted for occupational use (yes/no) of other types of pesticides (i.e., OPs, OCs, DTCs, paraquat, rotenone, carbamates, triflumizole, captan, and propargite, pesticides for which we have previously seen associations of ambient exposures or frequent household use with PD[10, 11, 16]). Second, we created different exposure categories combining different pesticide exposure measures.…”
Section: Methodsmentioning
confidence: 99%
“…In our California based case control study of PD,[9, 10] we conducted a detailed historical assessment of active occupational use of pesticides and personal protective equipment (PPE) use which we are reporting on for the very first time, while our previous reports relied on extensive information for other sources of pesticide exposure for this population, specifically, ambient pesticide exposures from agricultural applications at work places and residences and household pesticide use. Here, we present results for primarily farming-related occupational pesticide use self-reported by participants and complemented by information on chemicals from the California pesticide registration system.…”
Section: Introduction1mentioning
confidence: 99%
“…However, some studies have demonstrated deficits in degradation systems, linked to neurodegeneration. (Ritz et al 2016;Martella et al, 2016Tanner et al, 2014Marques et al, 2011). under normal conditions, where alpha-synuclein is mainly found at the synaptic terminal; (B) during normal aging, where alpha-synuclein can be found spread throughout the neuron; (C) in early onset PD, where alpha-synuclein is prone to aggregate; (D) in case of overexpression of alpha-synuclein,, leading to the spread out of the protein in the synaptic terminal and the soma; (E) when the gene is knocked down, leading to cell death (Benskey et al, 2016).…”
Section: Alpha-synucleinmentioning
confidence: 99%